Tropical herbivorous phasmids, but not litter snails, alter decomposition rates by modifying litter bacteria. Issue 4 (30th March 2018) - Prather, Chelse M.; Belovsky, Gary E.; Cantrell, Sharon A.; González, Grizelle
Abstract: Consumers can alter decomposition rates through both feces and selective feeding in many ecosystems, but these combined effects have seldom been examined in tropical ecosystems. Members of the detrital food web (litter‐feeders or microbivores) should presumably have greater effects on decomposition than herbivores, members of the green food web. Using litterbag experiments within a field enclosure experiment, we determined the relative effects of common litter snails ( Megalomastoma croceum ) and herbivorous walking sticks ( Lamponius portoricensis ) on litter composition, decomposition rates, and microbes in a Puerto Rican rainforest, and whether consumer effects were altered by canopy cover presence. Although canopy presence did not alter consumers' effects, focal organisms had unexpected influences on decomposition. Decomposition was not altered by litter snails, but herbivorous walking sticks reduced leaf decomposition by about 50% through reductions in high quality litter abundance and, consequently, lower bacterial richness and abundance. This relatively unexplored but potentially important link between tropical herbivores, detritus, and litter microbes in this forest demonstrates the need to consider autotrophic influences when examining rainforest ecosystem processes.